Re‐searching access: what do attempts at studying migration control tell us about the state?. (30th July 2019) - Kalir, Barak; Achermann, Christin; Rosset, Damian
Abstract : Contributors to this special issue realised that reflecting on experiences of getting access (or not) can tell us something important about the institutions we aimed to study and, more broadly, about the migration control field. Put differently, attempts at approaching and approximating state actors within a charged field exposed us to some of its most fundamental organising principles. We have, therefore, set ourselves the task in this issue of SA/AS to ask and answer the following question: What do attempts at studying migration control tell us about the state? Our exercise is, thus, squarely set as an attempt to intervene in a burgeoning debate around the ways in which the 'anthropology of the state' can develop. Both the issues at stake – the management of undesired others – and the field in which we conduct our studies, migration control administrations, are indeed changing to become acutely central to the governing of our societies. By gathering findings from different research projects across Europe, this special issue offers a comparative perspective on some of the most salient features of the migration control field from the eyes of ethnographic researchers in search of access. La recherche et l'accès : que nous disent les tentatives d'étudier le contrôle migratoire sur l'État?: Les contributrices et contributeurs à ce numéro thématique ont pris conscience qu'une réflexion sur nos expériences d'accès (ou non) permet d'identifier d'importantes caractéristiques des institutions que nous voulions étudier et, plus largement, sur le champ du contrôle migratoire. Autrement dit, nos tentatives d'approcher et d'approximer des acteurs étatiques au sein d'un champ sous tension nous ont exposés à certains de ses principes d'organisation les plus fondamentaux. Nous nous sommes, par conséquent, fixé pour tâche de répondre à la question suivante : que nous disent nos tentatives d'étudier le contrôle migratoire sur l'État? Notre exercice est donc clairement défini comme une tentative d'intervenir dans un débat naissant sur les moyens par lesquels « l'anthropologie de l'État » peut se développer. Tant les enjeux au cœur de nos recherches – la gestion des autres indésirables – que les terrains dans lesquels nous les menons, les administrations de contrôle migratoire, deviennent de plus en plus essentiels à la gouvernance de nos sociétés. En rassemblant les résultats de différents projets de recherche en Europe, ce numéro de SA/AS offre une perspective comparative sur certains des aspects les plus saillants du champ du contrôle migratoire du point de vue des chercheuses et chercheurs ethnographiques en quête d'accès.